Age-Graded Differences and Parental Influences on Adolescents’ Obligation to Obey the Law - Fine, Adam (Journal of developmental and life-course criminology, 2020)
Legal socialization is the study of how individuals develop their attitudes towards the law and its authorities. While research on perceptions of legal authorities has increased, studies have not adequately examined developmental trends in youths’ obligation to obey the law in particular.